Digestive Enzymatic Activity Profiles and Larval Growth Performance of Barramundi, Lates calcarifer (Bloch, 1790), From Indonesian and Australian Broodstocks - Wibawa, Gigih Setia; Haryanti, Haryanti; Kurniawan, Nia (Biotropika: Journal of Tropical Biology, 2024)
Barramundi fish is one of the most important aquaculture commodities, with cultivation challenges closely related to its survival and growth. There is still a lack of information on digestive enzymatic activity profiles and larval growth, and the use of Australian brooders rather than Indonesian brooders is still frequent. This study aims to investigate digestive enzymatic activity profiles and their correlation to the growth performance of barramundi larvae, Lates calcarifer (Bloch, 1790), originating from Indonesia and Australia. The digestive enzyme activity profile was evaluated using real-time quantitative polymerase chain reaction (RT-qPCR). First, larvae were reared in captivity till day 20 (20 dah). During this rearing, measurements of length and weight growth were done every day. Experiment data shows Australian fish larvae were greater than that of the Indonesian. Their digestive enzyme activity also confirmed that Australian larvae had more activity than Indonesian larvae.